2018
DOI: 10.3390/ijms19072068
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Product 6-Gingerol Inhibits Inflammation-Associated Osteoclast Differentiation via Reduction of Prostaglandin E2 Levels

Abstract: The natural product 6-gingerol, a major bioactive component of the rhizome of ginger (Zingiber officinale), is known to have several beneficial effects on health, including anti-inflammatory activity. The present study aimed to investigate the effects of 6-gingerol on osteoclast differentiation associated with inflammation. 6-Gingerol inhibited osteoclast differentiation in co-cultures of osteoblasts and osteoclast precursor cells in response to the pro-inflammatory cytokine, interleukin (IL)-1. However, it di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Extracts [69,70], essential oils [71], shogaols, gingerols [70], 6-gingerol [72] (i) Anti-inflammatory [69][70][71], (ii) Inhibited inflammation-associated osteoclast differentiation [72] Dang gui Angelica sinensis Oliv. Diels Extract [73], ethyl acetate fraction [74], ferulic acid, Z-ligustilide [75], calycosin [76] (i) Anti-inflammatory [75], (ii) Inhibited rheumatoid synovial fibroblast proliferation [74], (iii) Potential interleukin 6R inhibitor [76], (iv) Inhibited osteoclast differentiation [73] Shao yao, Bai shao yao, Chi shao yao…”
Section: Syndromes In 2018 Guidelinementioning
confidence: 99%
“…Extracts [69,70], essential oils [71], shogaols, gingerols [70], 6-gingerol [72] (i) Anti-inflammatory [69][70][71], (ii) Inhibited inflammation-associated osteoclast differentiation [72] Dang gui Angelica sinensis Oliv. Diels Extract [73], ethyl acetate fraction [74], ferulic acid, Z-ligustilide [75], calycosin [76] (i) Anti-inflammatory [75], (ii) Inhibited rheumatoid synovial fibroblast proliferation [74], (iii) Potential interleukin 6R inhibitor [76], (iv) Inhibited osteoclast differentiation [73] Shao yao, Bai shao yao, Chi shao yao…”
Section: Syndromes In 2018 Guidelinementioning
confidence: 99%
“…A key step involving in PGE2 production is the conversion of arachidonic acid to prostanoids catalyzed by cyclooxygenase-1 and-2 (COX-1, COX-2) [19]. Previous study have shown that 6-gingerol can inhibit the production of PGE2 and inflammation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Achyranthes bidentata polysaccharide, berberine sulphate, nitidine chloride, artesunate and so on were also found to be potential therapeutic candidates for the prevention or treatment of osteoporosis . Other studies also investigated the osteoporotic effects of compounds such as magnolol and polysaccharides …”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Other studies also investigated the osteoporotic effects of compounds such as magnolol and polysaccharides. [24][25][26][27][28] As one of BNPs, the compound of Asperpyrone A was isolated from Aspergillus niger with various biological activities including antitumour, antimicrobial and antioxidant. 10,11 Its effects on attenuating RANKL-induced osteoclast formation were identified by our F I G U R E 5 Asperpyrone A suppresses NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%